ID THEFT IN CYBERSPACE - Maxim DOBRINOIU (Challenges of the Knowledge Society)
Obtaining personal data, identification data, including data which allow the use of a electronic payment instrument, or any other data generated in the context of one person’s activities in the social, economic or financial life, without its consent or by deceit, if this occurs in computer systems or through electronic means of communications, should be considered as a crime and punished accordingly.